Impact of Nursing Curriculum on Clinical Competence and Nursing Practice: A Cross-Sectional Study of Selected Institutions in Nigeria - Chukwu, Lydia Ngozi; Ogbu, David Okoh (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
This study assessed the impact of the Nigerian nursing curriculum on clinical practice, focusing on its relevance, the integration of theory and practice, and areas requiring reform. Despite recent reforms by the Nursing and Midwifery Council of Nigeria (NMCN) to align nursing education with global standards, concerns persist regarding graduates' preparedness for modern healthcare demands. This survey aimed to evaluate the integration of theoretical knowledge with practical skills, assess the curriculum's effectiveness in clinical practice, and identify existing gaps. A cross-sectional descriptive survey was conducted among 231 registered nurses at the University of Abuja Teaching Hospital, Gwagwalada, using a structured questionnaire. Data were analyzed with descriptive and inferential statistics, alongside a thematic analysis of open-ended responses. Findings revealed that the curriculum received an overall "Very Good" rating (73%). It performed strongly in design and regulatory alignment (80%) but received lower ratings for institutional support and clinical exposure. While evidence-based practice and core nursing skills were adequately emphasized, the integration of modern healthcare technologies (34%) and community/public health nursing (52%) was limited, highlighting a persistent theory-practice gap. Major deficiencies included digital/technological competence (30%), community/public health preparation (25%), and leadership and advocacy training (20%). The study concludes that although the Nigerian nursing curriculum provides a solid theoretical foundation, it inadequately prepares graduates for real-world challenges, thereby slowing their progression along Benner’s novice-to-expert continuum. Recommendations include regular curriculum reviews, strengthened clinical training, the incorporation of digital health technology, expanded community-based experiences, and embedded leadership development. Addressing these gaps is essential for producing competent, confident, and practice-ready nurses capable of meeting Nigeria’s evolving healthcare needs.